Potential of Citronella Oil and Gum Rosin as Antimicrobial Agents in Floor Cleaner Liquid Against Salmonella thypi - Wa Ode Cakra Nirwana; Chandrawati Cahyani; Vivi Nurhadianty (Jurnal Teknik Kimia dan Lingkungan, 2023)
Some floor cleaner products on the market contain antimicrobial agents that are harmful to humans and the environment, such as benzalkonium chloride. Therefore, searching for a new antimicrobial agent that is relatively safe is a significant challenge. In this study, we investigated the best formula for making floor cleaner using citronella oil and gum rosin as antimicrobial agents. Its antimicrobial activity against Salmonella thypi was investigated and compared with that of a commercial floor cleaner containing benzalkonium chloride. Five concentrations and ratios of citronella oil and gum rosin were investigated. The quality of floor cleaner in terms of pH range and the stability of the emulsion in hard water was assessed according to SNI 06-1842-1995. The results showed that all formulas met the pH range required by SNI, except for formulas containing citronella oil alone. The emulsion in hard water was stable for all formulas. The antimicrobial activity increased with increasing concentrations of antimicrobial agents. Citronella oil exhibited higher antimicrobial activity than gum rosin. Benzalkonium chloride showed higher microbial activity than gum rosin but lower than citronella oil. The combination of citronella oil and gum rosin showed higher microbial activity by 1.1–2.4 times than formulas containing benzalkonium chloride. The optimum floor cleaner formula (a concentration of citronella oil and gum rosin of 2% with a ratio of 1:1) has an inhibition zone diameter of 22.2 mm.